Answer:
![y(t)\ =\ C_1.e^(-2t)+C_2e^t-\ t.(e^(-2t))/(3)-(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/9iq75z2u5j4vt1bq9vz292eodh6srxpxhf.png)
Explanation:
Given differential equation is,
y"+y'-2y=1
![=>\ (D^2+D-2D)y\ =\ 1](https://img.qammunity.org/2020/formulas/mathematics/college/kjpmqiqz95ges9ko53g5hyt32bi4l5q0p8.png)
To find the complementary function we will write,
![D^2+D-2=0](https://img.qammunity.org/2020/formulas/mathematics/college/rruqigqu8hkh82skpotairt2q709qe7ci6.png)
![=>\ D\ =\ (-1+√(1^2+4* 2* 1))/(2* 1)\ or\ (-1-√(1^2+4* 2* 1))/(2* 1)](https://img.qammunity.org/2020/formulas/mathematics/college/5jql5otyg61ay48r3hqxos11yg3lcfrmhy.png)
![=>\ D\ =\ -2\ or\ 1](https://img.qammunity.org/2020/formulas/mathematics/college/61q687ojr7tltlrc8vl922hm75s0xbq7y9.png)
Hence, the complementary function can be given by
![y(t)\ =\ C_1e^(-2t)\ +\ C_2e^t](https://img.qammunity.org/2020/formulas/mathematics/college/nle94h5xt93mjvzw0vph55hnc14jqfmrr7.png)
Let's say,
![y_1(t)\ =\ e^(-2t)\ \ =>y'_1(t)\ =\ -2e^(-2t)](https://img.qammunity.org/2020/formulas/mathematics/college/kxzgo7ql5j23k89228qy7c651qfz42nw4q.png)
![y_2(t)\ =\ e^(t)\ \ =>y'_2(t)\ =\ e^(t)](https://img.qammunity.org/2020/formulas/mathematics/college/6fu5jks6wzrypw5tmnfskf2on0nhqjdu12.png)
![g(t)\ =\ 1](https://img.qammunity.org/2020/formulas/mathematics/college/y0idgisvvbpealnda30179dpzf6r28cgbp.png)
Wronskian can be given by,
![W\ =\ y_1(t).y'_2(t)\ -\ y_2(t).y'_1(t)](https://img.qammunity.org/2020/formulas/mathematics/college/7j9xcxic2dxj7sno6d3ihv88t2uckdzvdx.png)
![=\ e^(-2t).e^(t)\ -\ e^(t).(-2e^(-2t))](https://img.qammunity.org/2020/formulas/mathematics/college/tubip30gmd59dke0zvzds3gpnlk7yq4qmw.png)
![=\ e^(-t)\ +\ 2e^(-t)](https://img.qammunity.org/2020/formulas/mathematics/college/c2wio44htj66hswrswl8guizrq7oqikz8y.png)
![=\ 3.e^(-t)](https://img.qammunity.org/2020/formulas/mathematics/college/wldm6z96kb4eczx0vu4fk82kfju3c7mvx7.png)
Now, the particular integral can be given by
![y_p(t)=\ -y_1(t)\int(y_2(t).g(t))/(W)dt\ +\ y_2(t)\int(y_1(t).g(t))/(W)dt](https://img.qammunity.org/2020/formulas/mathematics/college/75tnr44d9vkdcaa2b06nupembm9rcej7sl.png)
![=\ -e^(-2t)\int(e^t.1)/(3.e^(-t))+e^t\int(e^(-2t).1)/(3.e^(-t))dt](https://img.qammunity.org/2020/formulas/mathematics/college/73ez744ad64xvwvxoh6tno0n576aqcirle.png)
![=\ -e^(-2t)\int(1)/(3)dt+(e^t)/(3)\int e^(-t)dt](https://img.qammunity.org/2020/formulas/mathematics/college/j11p030k673gawrhf4ox42l6sbwfh0dl8w.png)
![=\ (-e^(-2t))/(3).t\ -\ (e^t)/(3).e^(-t)](https://img.qammunity.org/2020/formulas/mathematics/college/svfze8m5opuf66ncszfwvj5ds7ni40v1mr.png)
![=\ -t.(e^(-2t))/(3)-(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/o4jsjxxjkmosaxaz9rrgwek9osgpj9cxct.png)
Hence, the complete solution can be given by
![y(t)\ =\ C_1.e^(-2t)+C_2e^t-\ t.(e^(-2t))/(3)-(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/college/9iq75z2u5j4vt1bq9vz292eodh6srxpxhf.png)